2015
DOI: 10.1007/s00018-014-1814-x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid rafts: integrated platforms for vascular organization offering therapeutic opportunities

Abstract: Research on the nanoscale membrane structures known as lipid rafts is relevant to the fields of cancer biology, inflammation and ischaemia. Lipid rafts recruit molecules critical to signalling and regulation of the invasion process in malignant cells, the leukocytes that provide immunity in inflammation and the endothelial cells that build blood and lymphatic vessels, as well as the patterning of neural networks. As angiogenesis is a common denominator, regulation of receptors and signalling molecules critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 232 publications
0
29
0
Order By: Relevance
“…Besides temperature, cholesterol and Cer are two lipids requiring a thorough consideration in the context of phase separation. Cholesterol is a key component of membrane biology and the concept of its clustering into membrane domains is attractive to explain its different functions including (i) membrane fluidity via lipid ordering; (ii) membrane deformability by modulation of PM protein interactions at the interface with cortical cytoskeleton [52]; (iii) formation and stabilization of nanometric lipid assemblies, rafts and caveolae [40, 53], as signaling platforms [54-56]; and (iv) phase coexistence in artificial membranes [57-59]. Fig.…”
Section: Lateral Organization Of Lipids Into Submicrometric Domainsmentioning
confidence: 99%
“…Besides temperature, cholesterol and Cer are two lipids requiring a thorough consideration in the context of phase separation. Cholesterol is a key component of membrane biology and the concept of its clustering into membrane domains is attractive to explain its different functions including (i) membrane fluidity via lipid ordering; (ii) membrane deformability by modulation of PM protein interactions at the interface with cortical cytoskeleton [52]; (iii) formation and stabilization of nanometric lipid assemblies, rafts and caveolae [40, 53], as signaling platforms [54-56]; and (iv) phase coexistence in artificial membranes [57-59]. Fig.…”
Section: Lateral Organization Of Lipids Into Submicrometric Domainsmentioning
confidence: 99%
“…In contrast, cholesterol transbilayer distribution remains unclear; several studies, however, reached the same conclusion that a significant part (50-75 %) is distributed in the inner leaflet [5,6]. Membrane cholesterol plays key regulatory roles including (1) membrane fluidity via lipid ordering; (2) membrane deformability by modulation of plasma membrane protein interactions at the interface with cortical cytoskeleton [7]; (3) formation and stabilization of nanometric lipid assemblies, rafts and caveolae [2,4], as important signaling platforms [8][9][10]; and (4) phase coexistence in artificial membranes [11][12][13]. Cholesterol is, thus, a key component of membrane biology and the concept of its clustering into membrane domains is attractive to explain its different functions.…”
Section: Introductionmentioning
confidence: 99%
“…Integrin signaling is important as well for the control of Rho activity and can be modulated through mechanical changes in the cytoskeleton [ 85 ]. Also, it has been demonstrated that lipid rafts are mediating growth cone guidance in the angiogenetic process, through localized assembly of receptor-ligand interactions, the afterwards cytoskeletal rearrangement and local protein synthesis, including Src family kinases and Rho GTPases [ 86 ].…”
Section: Discussionmentioning
confidence: 99%